Rural Government Cooperation Intensity and Leadership in Fostering the Innovation Capabilities of Rural Microbusinesses - Wibowo, Ardy; Maula, Defia Ifsantin; Setiawan, Dani Fikri; Hisam, Muhammad (Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
Introduction: The growth of rural entrepreneurship significantly impacts economic growth and the well-being of rural communities. Background Problem: Innovation is crucial for entrepreneurs' success, with rural government playing a pivotal role in rural societies. Novelty: This study overviews the role of rural government in fostering entrepreneurial innovation, focusing on inter-organizational collaboration and the village head's leadership style. Research Method: Employing a quantitative survey methodology, the study undertook direct surveys of 300 rural micro- and small-scale entrepreneurs from diverse industries in Indonesia. A simple random sampling technique was used to ensure a representative sample of the population. Data were analyzed using Structural Equation Modeling—Partial Least Squares. Findings: The analysis reveals that rural government cooperation and transformative leadership positively influence entrepreneurs' perceptions of organizational support. In turn, perceived organizational support significantly impacts the desire for knowledge sharing and innovation capability enhancement. This study diverges from previous research by examining the mediating roles of knowledge sharing and perceived organizational support in innovation capability enhancement. It confirms that perceived organizational support is a vital mediator in the relationship between government cooperation intensity, transformational leadership, and innovation capability. Conclusions: The findings underscore the need for rural governments to practice effective cooperation and leadership and provide consistent support. Such strategies facilitate a supportive environment that fosters knowledge sharing and significantly boosts rural entrepreneurs' innovation capabilities.